Bone regeneration from mesenchymal stem cells (MSCs) and compact bone-derived MSCs as an animal model - Eiki Yamachika; Seiji Iida (Elsevier, 2013)
Mesenchymal stem cells (MSCs) have emerged as a promising alternative to traditional surgical techniques. The purpose of this review is to document the current state of research and identify future research directions. At present, no specific markers have been shown to specifically identify MSCs. The most commonly reported positive markers are CD105, CD90, CD44, CD73, CD29, CD13, CD34, CD146, CD106, CD54 and CD166. The most frequently reported negative markers are CD34, CD14, CD45, CD11b, CD49d, CD106, CD10 and CD31. Regarding the source of MSCs, bone marrow-derived MSCs are the most frequently studied MSCs in bone regeneration; however, no reports have demonstrated advantages of bone marrow-derived MSCs over other types of MSCs in bone regeneration. For the purpose of clinical use, serum-free media is recommended to avoid risks connected with the use of animal products. Attempts have been made to develop defined serum-free media for animal and human MSC growth; however, most products have demonstrated only limited performance. Tumorigenesis is the other major problem in MSC regeneration. It is strongly recommended to prepare MSCs for tissue regeneration at early passages to avoid potential chromosomal abnormalities.